DAMPAK KEPEMILIKAN MANAGERIAL, LARGE EXTERNAL SHAREHOLDERS TERHADAP STRUKTUR MODAL DALAM PERSPEKTIF TEORI KEAGENAN - Sri Sugarsi (Jurnal Bisnis dan Ekonomi, 2008)
The aims of this research are to provide empirical evidence about the effects of managementownership and ownership by large external shareholders on the capital structure of the firm, andalso to analyse effects of interaction between management ownership and ownership by largeexternal shareholders on the capital structure. This analysis is basically for perspective agencytheory.Population in this research are all manufacture industry firms which a listed in Jakarta StockExchange, during year 2000-2005. Method intake of sample is purposive sampling. Datacollecting done with cross-sectional, final sample consists of 128 firms a year. Data analyzingtechnique used 4 equation models with SPSS program. Examination to hypothesis is basicallydone after detecting outlier and test of classic assumption.Result of finding show that capital structure (Debt ratio) is positively related to managementownership and negatively related to ownership by large external shareholders. Furthermore, thepresence of large external shareholders acts to negate the positive relationship between debt ratioand management ownership not proved. Profta and Growta variables are negatively relativelyrelated to debt ratio and debt ratio is positively related to firm size, and significant.Key words: Capital structure; management ownership, Large external Shareholder, andAgency theory.